Reducing barriers to trauma inquiry in substance use disorder treatment - a cluster-randomized controlled trial - Annett Lotzin; Sven Buth; Susanne Sehner; Philipp Hiller; Silke Pawils; Franka Metzner; John Read; Martin Härter; Ingo Schäfer (BMC, 2019)
Abstract Background Despite the high rate of traumatic events in clients with substance use disorders, trauma exposure often remains undetected in a majority of treatment-seeking clients. Improving health professionals' knowledge and skills in the inquiry of traumatic events is therefore of utmost importance for appropriately addressing trauma-related treatment needs. However, professionals in substance use disorder treatment settings frequently report barriers to the inquiry about traumatic events, e.g., the fear of offending or harming the client. Such barriers should be addressed by trainings that aim to improve the systematic inquiry of traumatic events. Methods Using a cluster-randomized trial, we examined whether a one-day training in trauma inquiry ('Learning How to Ask') would reduce professionals' perceived barriers to trauma inquiry. One hundred forty-eight professionals working in outpatient substance use disorder treatment centers were randomized to an intervention (n = 72) or a control group (n = 76). The professionals in the intervention group received a one-day training plus a refresher session 3 months later, the professionals in the control group received no training. At baseline, and at 3-month and 6-month follow-up, professionals rated on a four-point Likert scale regarding how strongly they agreed with statements about six common barriers to trauma inquiry, namely 'Feeling uncomfortable when asking about traumatic events', 'Fear of offending the client', 'Fear of retraumatizing the client', 'Fear that client may terminate treatment', 'Unsure whether authorities have to be informed when perpetrator is known', and 'No trauma-specific treatment available in my local area'. Results The trained group experienced significant greater decreases in five of the six perceived barriers to the inquiry of traumatic events from baseline to 6-month follow-up than the control group ('Feeling uncomfortable when asking about traumatic events': b = − 0.32, 95% CI [− 0.52, − 0.12]; 'Fear of offending the client': b = − 0.33, 95% CI [− 0.56, − 0.09]); 'Fear of retraumatizing the client': b = − 0.45, 95% CI [− 0.69, − 0.22]; 'Fear that client may terminate treatment': b = − 0.28, 95% CI [− 0.49, 0.07]; 'No trauma-specific treatment available in my local area': b = − 0.25, 95% CI [− 0.51, − 0.01]). Conclusions Our findings provide first evidence that a one-day training in trauma inquiry is effective in reducing common barriers to trauma inquiry, which may in turn improve detection of traumatic events.